Behaviour Change in Agri-food Systems Transformation: a Review of Past Initiatives in Tunisia - Lestrelin, Guillaume; Jaouadi, Rahma; Braiki, Houssem; Hamrouni, Dhia; Alary, Veronique; Idoudi, Zied; Rekik, Mourad; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2023)
This country brief is an output of the Agroecology Initiative's Work Package 5, dedicated to understanding and subsequently influencing behavior change and actor agency to achieve its goals. It leverages insights from an inventory of agroecology-related initiatives and key informant interviews to extract lessons from previous initiatives in Tunisia. The assessment encompasses their strategies and approaches for behaviour change, actor motivations, theories of change, as well as the successes and failures encountered by these initiatives.